Resveratrol elicits anti-colorectal cancer effect by activating miR-34c-KITLG in vitro and in vivo. Issue 1 (December 2015) - Yang, Shu; Li, Wenshuai; Sun, Haimei; Wu, Bo; Ji, Fengqing; Sun, Tingyi; Chang, Huanhuan; Shen, Ping; Wang, Yaxi; Zhou, Deshan
Abstract Background Silence of the tumor suppressormiR-34c is implicated in the development of colorectal cancer (CRC). For the past few years, Resveratrol (Res) has been introduced to oncotherapies alone or with traditional chemotherapeutic drugs. However, the study of molecular mechanism involved in the anti-CRC effect of Res is still ongoing. Methods The anti-CRC effect of Res alone or with Oxaliplatin (Oxa) was determined by cell viability assay, soft agar colony formation assay, flow cytometry and real-time cellular analyzer in HT-29 (p53 + ) and HCT-116 (p53 − ) CRC cell lines. Expressions of miR-34c and its targets were detected by qPCR and/or western blot. To evaluate the role ofmiR-34c in anti-CRC effect by Res alone or with Oxa, miR-34c was up or down-regulated by lentiviral mediation or specific inhibitor, respectively. To investigate how miR-34c was increased by Res, the methylation status of miR-34c promoter was detected by MSP. The tumor bearing mouse model was established by subcutaneous injection of HCT-116 cells to assess anti-CRC effect of Res alone or with Oxa in vivo. IL-6 and TNF-α in xenografts were detected by ELISA. Results Res inhibited cell viability, proliferation, migration and invasion as well as promoted apoptosis both in HT-29 and HCT-116 CRC cells. The anti-CRC effect of Res was partially but specifically through up-regulatingmiR-34c which further knocked down its target KITLG; and the effect was enhanced in the presence of p53 probably through inactivating PI3K/Akt pathway. Besides, Res sensitized CRC cells to Oxa in amiR-34c dependent manner. The xenograft experiments showed that exposure to Res or Oxa suppressed tumor growth; and the efficacy was evidently augmented by the co-treatment of Res and Oxa. Likewise, miR-34c level was elevated in xenografts of Res-treated mice while the KITLG was decreased. Finally, Res clearly reduced IL-6 in xenografts. Conclusion Res suppressed CRC by specifically activatingmiR-34c -KITLG in vitro and in vivo; and the effect was strengthened in the presence of p53. Besides, Res exerted a synergistic effect with Oxa in amiR-34c dependent manner. We also suggested that Res-increasedmiR-34c could interfere IL-6-triggered CRC progression.